Zur „psycholinguistischen Einheit“ im Zweitsprachenerwerb - Figas, Janusz (Studia Germanica Posnaniensia, 2018)
The author concentrated his attention on the process of bringing up to date the acquired patterns of verbal behaviour as a behaviour (action, activity) which is a directed (purposeful) one. In the research of factors conditioning self-acting of construction of plans (bringing up to date of structures) of verbal behaviour what is concerned is the individual ability (skill) of using the 'second' language (Zweitsprache, L2). The basis of a model of production of linguistic utterances is a cybernetic system of self-regulation of TOTE type (according to Miller/Galanter/Pribram 1980, Polish edition). That is why a common denominator to which the particular, above quoted attitudes are resolved, becomes like in A. A. Leont'ev's (1975, German edition) a psycholinguistic unit. As the subject of research of the so called performance not the formal description of structures is postulated but the factors which condition directing of a given structure to the goal of the block of self-acting production. This approach is born from practical need of influencing and transforming (processing) linguistic information in the processes of language perception and production in a thinking (intelligent) individual in the second language acquisitio